A research framework for evaluating the competitiveness of developing countries an example of the Philippines - Wang, Tai-Yue (Asia Pacific management review)
The Philippines, a country was with glory in Southeast Asia, has determined to return to being thriving and prosperous in the global economy. This paper presents a different framework for evaluating the national competitiveness of the Philippines. The analysis is from the Philippines' viewpoint, in terms of the categories of economic performance, technology development, human resource, management, and productivity. In order to reflect the domestic and international perspective, the weights for each category and their subordinated sub-categories were solicited from experts in various industries, governmental institutions, and academia in the Philippines. The main suggestions are that the Philippines government should maintain stable economic policies and sustain political stability to attract more foreign direct investments. The implications of national competitiveness in each category are also discussed in this study.